2005
DOI: 10.1590/s0328-03812005000100010
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Dentocarpus silvai silvai Dusbabek & Cruz, 1966 (Acari: Chirodiscidae) em duas espécies de molossídeos (Mammalia: Chiroptera) no estado do Rio de Janeiro, Brasil

Abstract: Occurence of Dentocarpus silvai silvai, Dusbabek & Cruz, 1966 (Acari: Chirodiscidae) on two molossids (Mammalia: Chiroptera) species in Rio de Janeiro state, Brazil -In 2001 mites from three bats were collected, Molossus ater at Silva Jardim municipality and from Molossus molossus at Rio de Janeiro municipality, both in the Rio de Janeiro state. The mites where identified as Dentocarpus silvai silvai (Acari: Chirodiscidae), this being the first report of this mite species in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…Among the mites caught there were six free larvae, a copulatory nymph, six adult males and five adult females, two of which containing visible larvae inside their idiosoma (Figure 1). The larvae inside the females' idiosoma showed the gnathosoma arranged to the posterior side, as observed by Fonseca et al (2005) in D. silvai silvai, which corroborates the hypothesis of viviparity among chirodiscid mites (GUERRERO, 1992). For five mites, the development stage could not be identified because of damage that occurred during the bleaching process.…”
Section: Research Notesupporting
confidence: 78%
See 3 more Smart Citations
“…Among the mites caught there were six free larvae, a copulatory nymph, six adult males and five adult females, two of which containing visible larvae inside their idiosoma (Figure 1). The larvae inside the females' idiosoma showed the gnathosoma arranged to the posterior side, as observed by Fonseca et al (2005) in D. silvai silvai, which corroborates the hypothesis of viviparity among chirodiscid mites (GUERRERO, 1992). For five mites, the development stage could not be identified because of damage that occurred during the bleaching process.…”
Section: Research Notesupporting
confidence: 78%
“…According analysis realized by Labrzycka (2006) about morphology and biological adaptation of fur mites in Poland, it was also observed that chirodiscids are commonly found on the hair of the posterior area of bats and rarely on the head or near the ears. Remaining on the longer hairs located on the bats' back may be a way in which the parasites avoid removal through licking, as a cleaning method used by the hosts (FONSECA et al, 2005). These hairs are thicker than the others, thus allowing better lift provided by the two pairs of legs that are modified to clasp the host's hair.…”
Section: Research Notementioning
confidence: 99%
See 2 more Smart Citations